Applying the mean-variance framework: portfolio optimization and comparative performance analysis in the emerging Colombian capital market - González-Bueno, Jairo; Tamošiūnienė, Rima; Gómez Morales, Camilo; Rueda-Barrios, Gladys (Business, Management and Economics Engineering, 2025)
Purpose – this paper adopts the mean-variance approach in optimizing portfolios within the Colombian capital market, a setting full of complications such as lack of liquidity and market concentration. It delivers actionable messages for emerging market stakeholders and formulates guidance aimed at enhancing risk-adjusted returns and informing portfolio management in markets with similar structural and economic conditions. Research methodology – a bi-objective mean-variance model has been used for analyzing the stock prices of 17 stocks on a weekly basis from 2009–2024. Annual rebalancing has made the portfolio responsive to changes in the market, considering the Sharpe ratio as the benchmark to assess risk-adjusted performance. Findings – optimized portfolios in Colombia outperformed traditional investment funds by realizing better returns while having a balanced risk. Surely, this shows that the model is able to be flexible and react to changes in fluctuation, capture sectoral opportunities, and perform amazingly in a dynamic market. Research limitations – focusing on adaptability and real-time rebalancing in this work can establish a basis on which future research will operate, refining optimization strategies that incorporate advanced risk measures such as CVaR. Practical implications – the results present an effective and flexible tool for investors to optimize their portfolios in respect of risk diversification and sustainable returns, considering liquidity constraints and market turmoil. Originality/Value – this research connects theory and practice and demonstrates the flexibility of the mean-variance model in emerging economies. It emphasizes novelty in portfolio optimization solutions and further development of strategies in sophisticated financial conditions.